2013
DOI: 10.1038/srep01970
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering of yellow betalain pigments beyond the species barrier

Abstract: Betalains are one of the major plant pigment groups found in some higher plants and higher fungi. They are not produced naturally in any plant species outside of the order Caryophyllales, nor are they produced by anthocyanin-accumulating Caryophyllales. Here, we attempted to reconstruct the betalain biosynthetic pathway as a self-contained system in an anthocyanin-producing plant species. The combined expressions of a tyrosinase gene from shiitake mushroom and a DOPA 4,5-dioxygenase gene from the four-o'clock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
1
33
0
2
Order By: Relevance
“…Microbial community in gastrointestinal tract (GIT) related to the functions of host, including maintaining host health, improving performance, reducing environmental pollution, and ensuring food and animal products’ safety12345. Meanwhile, fecal microbiome also reflects feed conversion, gut pathogen and parasite colonization and immune system activity of host678.…”
mentioning
confidence: 99%
“…Microbial community in gastrointestinal tract (GIT) related to the functions of host, including maintaining host health, improving performance, reducing environmental pollution, and ensuring food and animal products’ safety12345. Meanwhile, fecal microbiome also reflects feed conversion, gut pathogen and parasite colonization and immune system activity of host678.…”
mentioning
confidence: 99%
“…In another recent study, betalain biosynthesis was achieved in non-betalain accumulating plants viz. Nicotiana tabacum and A. thaliana cell cultures by combined expression of Lentinula edodes TYR and M. jalapa DOD (Nakatsuka et al, 2013). This study revealed the possibility of engineering betalain biosynthesis across species barrier.…”
Section: Mutual Exclusiveness Of Anthocyanins and Betalainsmentioning
confidence: 80%
“…Although single ancestor origin of betalains and anthocyanins is being strengthened by betalain biosynthesis in anthocyanin producing plants after introduction of TYR and DOD (Nakatsuka et al, 2013), or DOD alone (Harris et al, 2012), and its regulation by a slightly different anthocyanin-type MYB protein (Hatlestad et al, 2015), pigmentation trait is prone to reversals (Brockington et al, 2011). Apart from transcriptional control, mutual exclusiveness of these pigments could be, plausibly, explained by biosynthesis regulation through metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…However, they can exist together by genetic engineering strategy [30,31]. Chalcone isomerase (CHI) and chalcone synthase (CHS) were the upstream enzymes of the anthocyanin biosynthesis pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes involved in betalain biosynthesis in higher plants are usually divided into three classes, namely tyrosinase (TYR), 4,5-dihydroxy-phenylalanine (DOPA)-dioxygenase (DOD), and glucosyltransferases (GTs). TYR plays a key role in hydroxylation and oxidation to form L-DOPA, cyclo -DOPA, tyr-betaxanthin and dopaxanthin that are the pivotal precursors of betalain biosynthesis [12,29,31,32,33]. TYR sequences have been obtained from Phytolacca americana [34], Spinacia oleracea [35] and Suaeda salsa [36].…”
Section: Introductionmentioning
confidence: 99%